Men Shall Be Lovers of Self, Money and Pleasure (II Timothy 3:2, 4): A Contemporary Discourse on the Apostle Paul's Prophecy of the End Times - Oluwatoba, Rotimi Paul; Akeju, Gabriel O.; Ampitan, Afolabi J. (Universitas Pelita Harapan, 2024)
The present time in Nigeria and globally has been more perilous than ever, characterized with bizarre occurrences within the church and the larger society. This study explores the Pauline eschatological prediction of the perilous times when men will become lovers of self, lovers of money, and lovers of pleasure more than God (II Timothy 3:1, 2 & 5). Experiential and theological methodologies were adopted for generating qualitative primary and secondary data. The theological aspect of the research employed the tools of biblical exegesis, textual analysis, and literatures. The experiential aspect involved in-depth interviews (IDIs), observations, social media contents and Focused Group Discussions (FGDs) to access current events and personalized experiences of respondents who were purposively selected from within and outside the church. The results were discussed in the light of Christian theology, social ethics and Pastoral ministry. The Nigerian society is evidently witnessing the perilous times when love of self, money and pleasure will become the untoward defining features of human society and sadly too, of men that profess the faith. Transactional gospel, gimmickry, merchandize of holy things, and self-indulgent love of money are rife in the contemporary church. Ostentatious lifestyles, lack of support for the minister at the local church, and false messages on material blessings are what trap church ministers and laypersons in this end-time evil. The context and practice of ”˜full time’ ministry when the local assembly is not able to support its minister is a challenge that predisposes some to ”˜Simoniacal’ presentations, offering the gifts of God for monetary gain. Sound biblical teachings to protect the people of God and expose the mercenary spirit in sacred function is the local church most potent weaponry.